The electrochemistry of simple inorganic molecules in room temperature ionic liquids - Silvester, D; Rogers, E; Barrosse-Antle, L; Broder, T; Compton, R (2008)
The electrochemistry of simple inorganic compounds in room temperature ionic liquids (RTILs) is reviewed and some new work in this area is presented. This paper focuses on the comparison between electrochemical behaviour in RTILs and in conventional aprotic solvents. Some compounds (iodides, O2, NO2, SO2, NH3) display similar reactions and mechanisms in RTILs as in aprotic solvents (as is observed for organic compounds). However other species (nitrates, PCl3, POCl3) show remarkably different behaviour to traditional solvents. This makes RTILs very promising media for the study of inorganic compounds, and highlights the need for more investigations in this exciting area. ©2008 Sociedade Brasileira de Química.